Investigating the biomechanical validity of the V-spine angle technique in cricket fast bowling - Ferdinands, R. E. D.; Singh, U. (International Journal of Sports Science & Coaching, 2023)
The effective utilisation of braking ground reaction forces is considered an essential biomechanical characteristic of fast bowling in cricket. The configuration of the trunk and legs during the delivery stride phase has been hypothesised to increase braking forces, causing the upper body segments to increase their angular momentum and thereby increase ball release speed. This study investigated the relationship between V-spine angle, front shank angle (plant angle) and front knee angle with braking ground reaction forces and ball release speed. Three-dimensional kinematic and kinetic analyses were performed for 17 male pace bowlers (17.2 ± 1.7 years) of New South Wales grade club level using data from a Cortex 2.0 motion analysis system (200 Hz) and Kistler force plates (1000 Hz). V-spine angle was strongly and significantly correlated with braking ground reaction force (r = -0.691), plant angle (r = -0.806) and front knee angle (r = -0.606). In addition, stepwise multiple linear regression analysis revealed that front shank angle was the strongest predictor of braking ground reaction force. The data suggests that V-spine angle and plant angle may play an important role in generating high braking ground reaction forces in bowling, with the front knee angle possibly playing a supporting role. Coaches may need to consider these findings when assessing the techniques of pace bowlers.